Vital signs : perspectives on the health of American campaigning - Dulio, David A. (Brookings Institution Press, 2005)
"Through analysis of the 2004 presidential campaigns of George W. Bush and John F. Kerry, explores the strengths and weaknesses of the current U.S. campaign system and possible approaches to improving campaign conduct"--Provided by publisher
Keywords: Presidents -- United States -- Election -- 2004.; United States -- Politics and government -- 2001-; Political campaigns -- United States -- Case studies.; United States -- Politics and government -- 2001-2009.; États-Unis -- Politique et gouvernement -- 2001-2009.; POLITICAL SCIENCE -- Political Process -- General.; POLITICAL SCIENCE -- Political Process -- Elections.; Political campaigns; Politics and government; Presidents -- Election; United States; Since 2001; Electronic books.; Case studies